2010
DOI: 10.1096/fj.09-150862
|View full text |Cite
|
Sign up to set email alerts
|

Two haplotypes of the P2X7receptor containing the Ala‐348 to Thr polymorphism exhibit a gain‐of‐function effect and enhanced interleukin‐1β secretion

Abstract: The P2X(7) receptor is an ATP-gated cation channel expressed in immune cells and plays a role in proinflammatory cytokine release from monocytes and macrophages. This study investigated the coinheritance of 12 functionally relevant single nucleotide polymorphisms (SNPs) in the human P2X(7) gene (P2RX7), and the functional effect of each singly and in combination was assessed by measurements of ATP-induced currents and ethidium(+) uptake. Genotyping of 3430 Caucasian subjects identified 4 common haplotypes in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
196
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(217 citation statements)
references
References 60 publications
(105 reference statements)
20
196
1
Order By: Relevance
“…The allele frequencies for the Tyr315Cys and Ser242Gly polymorphism in our population were almost identical to the previously published data Stokes et al [26]. Both SNPs were shown to be in HWE, indicating a valid population for current study.…”
Section: Discussionsupporting
confidence: 91%
“…The allele frequencies for the Tyr315Cys and Ser242Gly polymorphism in our population were almost identical to the previously published data Stokes et al [26]. Both SNPs were shown to be in HWE, indicating a valid population for current study.…”
Section: Discussionsupporting
confidence: 91%
“…Haplotype analysis of P2X7 genotypes identified 17 haplotypes with population frequencies 41.0 % (Table 4). Grouping the haplotypes based on the haplotype blocks containing the 1068, 1096, 1405 and 1513 polymorphisms as described by Stokes et al 30 showed similar haplotype frequencies between the Australian cohort and the DOPS cohort. Aggregating patients into a group of haplotypes carrying 'high-risk' loss-of-function variants showed the same accelerated BMD loss as for the Group A defined above on the basis of SNPs (data not shown).…”
Section: P2x7 Gene Polymorphisms and Bone Nr Jørgensen Et Almentioning
confidence: 79%
“…Both P2X7-2 and P2X7-4 contain the Ala348Thr polymorphism and this variant is critical for the gain-of-function effect. 30 Analysis showed a lesser fracture rate for subjects with one or two of this gain-of-function allele.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations